Avtorska dela na univerzi: konferenčni zbornik / IX. posvet Pravo in ekonomija, 2. december 2016, Maribor (University of Maribor Press, 2017)
Copyrighted works at the university: Conference Papers / IX. Conference Law and Economics, December 2th, 2016, Maribor. Employees and students at the universities are facing numerous problems coupled with copyrighted works created in the course of pedagogical, research and educational process. The collected paper consists of several papers related to this topic: the attempt to define copyrighted works of employees created within the scope of employment; analysis of lawful reproduction of copyrighted works in the context of copyright restrictions; digitalisation of copyrighted works and their dissemination for the educational purposes; definition of academic plagiarism; analysis of proposal for a directive on copyright in the digital market and its impact on universities relations; analysis of a quality of scientific journals in which scientific works of employees at the universities are published and open access of such works; and the possibility to predict students’ success with special emphasis of copyright protection of databases and the protection of students’ personal data. The main reasons for problems arising at universities relating to copyright are ambiguous legal rules and their insufficient adjustment to modern technology. Thus, clearer rules should be adopted considering the definition of copyrighted works created in the course of employment and copyright restrictions for educational purposes should be adjusted to modern teaching approaches.